Inferring Life History Characteristics of the Oceanic Whitetip Shark Carcharhinus longimanus From Vertebral Bomb Radiocarbon - Passerotti, Michelle S.; Andrews, Allen H.; Natanson, Lisa J. (Frontiers in Marine Science, 2020)
Oceanic whitetip sharks Carcharhinus longimanus are a cosmopolitan epipelagic species that was once prolific throughout the tropics and subtropics but was recently listed as Critically Endangered by the IUCN and as Threatened under the United States Endangered Species Act. Although historically conspicuous in oceanic fisheries catches, relatively little is known about their habitat use, movement, and life history during migration. Given the paucity of data on migratory patterns and lack of age estimate validation available for this species, we evaluated vertebral growth bands for bomb radiocarbon (14C) patterns to derive additional information on these metrics. Individual growth bands (n = 62) were milled from vertebrae of eight individuals caught in the northwestern Atlantic Ocean. Age estimates based on vertebral growth bands ranged 1 – 13 years, with capture dates spanning 1978 – 1983. Plots of vertebral ∆14C relative to regional coral, shark, and fish otolith reference curves suggest age estimates based on presumed annual growth bands were accurate, although specimens were not old enough to capture the most informative portion of the bomb radiocarbon reference period. The magnitude of ∆14C varied among individuals, and individual chronologies demonstrated semi-cyclic patterns of ∆14C depletion and subsequent enrichment, which may be indicative of changes to diet as a function of migratory patterns and is supported by recently published telemetry, diet, and stable isotope studies. Although preliminary in nature, these data provide some evidence that ∆14C patterns in vertebrae can serve as a multi-purpose tool for life history studies of oceanic sharks.